The Role of Metabolic Changes in Shaping the Fate of Cancer-Associated Adipose Stem Cells - Cantini, Giulia; Di Franco, Alessandra; Mannelli, Massimo; Scimè, Anthony; Maggi, Mario; Luconi, Michaela (Frontiers in Cell and Developmental Biology, 2020)
Adipose tissue in physiological and in metabolically altered conditions (obesity, diabetes, metabolic syndrome) strictly interacts with the developing tumors both systemically and locally. In addition to the cancer-associated fibroblasts, adipose cells have also recently been described among the pivotal actors of the tumor microenvironment responsible for sustaining tumor development and progression. In particular, emerging evidence suggests that not only the mature adipocytes but also the adipose stem cells are able to establish a strict crosstalk with the tumor cells, thus resulting in a reciprocal reprogramming of both the tumor and adipose components. This review will focus on the metabolic changes induced by this interaction as a driver of fate determination occurring in cancer-associated adipose stem cells (CA-ASCs) to support the tumor metabolic requirements. We will showcase the major role played by the metabolic changes occurring in the adipose tumor microenvironment that regulates adipose stem cell fate and consequently cancer progression. Our new results will also highlight the CA-ASC response in vitro by using a coculture system of primary ASCs grown with cancer cells originating from two different types of adrenal cancers (adrenocortical carcinoma and pheochromocytoma). In conclusion, the different factors involved in this crosstalk process will be analyzed and their effects on the adipocyte differentiation potential and functions of CA-ASCs will be discussed.